METHODOLOGICAL PRINCIPLES OF ENERGY MANAGEMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF WOODWORKING INDUSTRY ENTERPRISES - Maksymiv, Volodymyr; Andrashek, Yosyp; Shchupakivskyy, Roman (Forestry, Forest, Paper and Woodworking Industry, 2011)
In this article, we consider the issue of working out energy efficiency strategy at woodworking enterprises as a constituent part of energy management. The role it plays and the place it occupies in the global strategy of sustainable development of enterprises have been defined; also characterized here are the main stages of shaping energy conservation policy as well as energy management in terms of integrated approach to environmental management.